Tourism and Welfare Ethics, Responsibility and Sustained Well-being - Hall, Derek (CABI, 2014)
The book elaborates ideas the authors first presented in the paper, ‘Towards a welfare focus for tourism research’, published in Progress in Tourism and Hospitality Research in 1996 (Hall and Brown, 1996). Some of the material in Chapter 6 is derived from research part-funded by the Scottish Executive Environment and Rural Affairs Department (SEERAD) and undertaken at the Scottish Agricultural College (SAC).